Avaliação de marcadores clínicos e imunológicos de idosos e portadores de artrite reumatóide na pandemia da COVID-19 - Rabelo, Cristina Ferreira (2023)
INTRODUCTION: The COVID-19 pandemic, known as coronavirus disease 2019, is an infectious disease caused by a novel coronavirus called SARS-CoV-2. This virus, derived from the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), leads to a highly contagious disease capable of inducing pneumonia and severe acute respiratory syndromes (SARS). Certain populations, particularly the elderly, are more susceptible to developing severe manifestations of the disease. OBJECTIVE: Investigate clinical and immunological characteristics of elderly patients with Rheumatoid Arthritis (RA) during COVID-19 pandemic and compare these findings with elderly individuals without autoimmune diseases and without the use of immunosuppressive agents (control group). METHODOLOGY: The study involved the participation of 23 elderly individuals with RA and 21 elderly individuals without autoimmune diseases or the use of immunosuppressive medications. This research followed a cross-sectional, controlled design, where clinical and immunological markers were investigated and compared between the two groups. The study population consisted of patients over 60 years of age receiving care at the outpatient clinics of Hospital São Lucas (HSL) affiliated with the Pontifical Catholic University of Rio Grande do Sul (PUCRS) and at the PUCRS Clinical Center. Clinical assessments were conducted through presencial appointment which included physical examinations and standardized questionnaires. The analysis of hematological, biochemical, and systemic inflammation markers followed the established protocols of the clinical analysis laboratory at HSL. Flow cytometry was employed for immunophenotyping and the identification of subpopulations of peripheral blood mononuclear cells (PBMCs). The recruitment of participants occurred between June 2021 and May 2023. RESULTS: The mean age of patients with RA was 70.6 years (± 4.7) and that of controls was 77.0 years (± 10.8). The observed disparity in age between these two groups was determined to be statistically significant, and this discrepancy was taken into consideration in the comparative analyses conducted.. Other clinical characteristics, such as the presence of comorbidities, depression, and frailty assessment rates, were found to be similar across both groups. It is worth noting that all individuals diagnosed with RA were utilizing immunosuppressants. Elderly individuals with RA exhibited lower adherence to social isolation measures and the use of masks at this point in the pandemic. However, but they had greater exposure to booster doses of anti-SARS-CoV2 vaccines, and the clinical events related to the COVID-19 pandemic were comparable between the RA and control groups. Importantly, patients with RA did not necessitate additional hospital care, medical consultations, or intensive care unit management. Moreover, there were no disparities in the reports of acute flu syndrome in the month preceding the interviews. The groups demonstrated homogeneity in terms of lipid profile, renal function, glycated hemoglobin levels, as well as absolute lymphocyte and neutrophil counts. Furthermore, it was observed that RA patients had lower albumin levels in comparison to the control group. Notably, higher frequencies of certain CD4+ T Lymphocyte (LT) subpopulations, including CD3+CD4+CD25+, CD4+CTLA4+, and CD4+PD1+CTLA4+, were identified in individuals with RA. However, no distinctions were found between the total CD4+ LT, total CD8+ LT, NKT LT (known as NKT cells), monocytes, or total B Lymphocyte (LB) populations. Interestingly, the transitional LB subpopulation, characterized by CD19+CD27-CD38hi, was found to be reduced in individuals with RA. In conclusion, this study sheds light on various aspects of elderly individuals with RA in the context of the COVID-19 pandemic and provides insights into immune checkpoints, activated T lymphocytes, and transitional B lymphocytes. CONCLUSIONS: From a clinical standpoint, patients with RA did not experience a worsened condition during this stage of the pandemic and within the outpatient setting, even thoughRA patients exhibited a more activated and more exhausted TL profilein comparison to elderly individuals without of RA. The population of transitional BL was reduced in the RA group , which may suggest that treatment of the disease can influence the immune response to vaccines via this route. RA and the use of immunosuppressive drugs have the potential to alter lymphocyte subpopulations.